2017
DOI: 10.1007/s10526-017-9825-9
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of tomato gray mold caused by Botrytis cinerea by using Streptomyces spp.

Abstract: Streptomyces is a genus known for its ability to protect plants against many pathogens and various strains of this bacteria have been used as biological control agents. In this study, the efficacy of Streptomyces philanthi RM-1-138, S. philanthi RL-1-178, and S. mycarofaciens SS-2-243 to control various strains of Botrytis cinerea was evaluated both in vitro and in vivo.In vitro studies using confrontation tests on PDA plates indicated that the three strains of Streptomyces spp. inhibited the growth of 41 stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Occurrence of chemical fungicide-resistant B. cinerea isolates in many countries and environment concerns due to frequent fungicide usages have urged to find eco-friendly alternatives for controlling grey mould for a sustainable horticulture ( Fan et al, 2016 ; Jacometti et al, 2010 ; Saito et al, 2019 ). Antagonistic microbes ( Bacillus subtilis , Streptomyces philanti , Fusarium equiseti ), plant essential oils (origanum oil, thyme oil) and plant defencepriming agents (β-aminobutyric acid, hexanoic acid) have been suggested to manage tomato grey mould on leaves and fruits eco-friendly ( Ben-Jabeur et al, 2015 ; Boukaew et al, 2017 ; Chen et al, 2019 ; Luna et al, 2016 ; Mónaco et al, 2009 ; Soylu et al, 2010 ; Vicedo et al, 2009 ).…”
mentioning
confidence: 99%
“…Occurrence of chemical fungicide-resistant B. cinerea isolates in many countries and environment concerns due to frequent fungicide usages have urged to find eco-friendly alternatives for controlling grey mould for a sustainable horticulture ( Fan et al, 2016 ; Jacometti et al, 2010 ; Saito et al, 2019 ). Antagonistic microbes ( Bacillus subtilis , Streptomyces philanti , Fusarium equiseti ), plant essential oils (origanum oil, thyme oil) and plant defencepriming agents (β-aminobutyric acid, hexanoic acid) have been suggested to manage tomato grey mould on leaves and fruits eco-friendly ( Ben-Jabeur et al, 2015 ; Boukaew et al, 2017 ; Chen et al, 2019 ; Luna et al, 2016 ; Mónaco et al, 2009 ; Soylu et al, 2010 ; Vicedo et al, 2009 ).…”
mentioning
confidence: 99%
“…These two diseases have mainly occurred in the aboveground parts of plants, which seriously threatens plant growth and development [ 25 ]. Boukaewet reported that Streptomyces is a genus known for its ability to protect plants against many pathogens and various strains of this bacteria have been used as biological control agents [ 26 ]. At present, the prevention and treatment of these two diseases are mainly based on chemical control, but the long-term use of chemical fungicides will lead to food safety, environmental pollution, and pathogenic bacterial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various antagonistic micro-organisms, Streptomyces spp. have been successfully evaluated as biocontrol agents against phytopathogens as they of produce both VOCs (Wan et al 2008;Li et al 2010Li et al , 2012Boukaew et al 2013Boukaew et al , 2019Yang et al 2018) and antimicrobial metabolites (Li et al 2011;Boukaew et al 2011Boukaew et al , 2017Shakeel et al 2018) with diverse biological activities. Numerous literature reports have shown that VOCs have significant antifungal activity against fungal pathogens (Minerdi et al 2009;Ando et al 2010;Glare et al 2012;Cordovez et al 2015;Gotorvila et al 2017).…”
Section: Introductionmentioning
confidence: 99%